Descent for regular epimorphisms in Barr exact Goursat categories - Janelidze, George (2009)
We show that the category of regular epimorphisms in a Barr exact Goursat category is almost Barr exact in the sense that (it is a regular category and) every regular epimorphism in it is an e ective descent morphism.